QM-MM investigation of the reaction products between nitroxyl and O2 in aqueous solution - Guardia, Carlos Manuel Alberto (2008)
By means of combined quantum-classical molecular (QM/MM) dynamics simulations, we investigated the structural properties and the vibrational spectra in aqueous solution of four possible intermediate species of the oxidation of nitroxyl (HNO/NO-) by dioxygen, the cis- and trans-isomers of peroxynitrous acid and nitroxyl-dioxygen adduct. Our study suggests that Raman spectroscopy will provide signals for discrimination between the peroxynitrous acid isomers from both adducts, and that infrared spectroscopy will probably assist the discrimination between the cis-peroxynitrous acid isomer from the other compounds considered. This application of hybrid simulation methods highlights the benefits of explicit solvent representations.